Strategi solve it dan kemampuan pemecahan soal cerita pada siswa: Menguji moderasi working memory, inhibitory control dan shifting: Solve it strategies and story problem solving abilities in students: Testing working memory moderation, inhibitory control and shifting - Siregar, Nani Restati; Wimbarti, Supra; Kusrohmaniah, Sri (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
The current research aims to determine the effect of (1) the solve its strategy on the ability to solve math story problems moderated by working memory; (2) the solve its strategy on the ability to solve math story problems moderated by inhibitory control; (3) the solve its strategy on the ability to solve math story problems moderated by shifting. This experimental research used an untreated control group design model with a dependent pretest and posttest. Participants in the research were students being 4th-grade elementary school students in the city of Yogyakarta. The ability to solve story problems was measured using the test of mathematical ability (TOMA), the backward digit span task to measure working memory capacity, and the matching familiar figure test to measure inhibitory control and shifting capacity using the Wisconsin card sorting test. Data analysis uses partial least squares (PLS). The research results showed that only the moderating effect of inhibitory control was proven to support the influence of the solve-it strategy on the ability to solve math story problems. Implications for further research are discussed.